Polycomb group genes are required to maintain a binary fate choice in the Drosophila eye. - Finley, J.K.; Miller, A.C.; Herman, T.G. (Neural Development, 2015)
Identifying the mechanisms by which cells remain irreversibly committed to their fates is a critical step toward understanding and being able to manipulate development and homeostasis. Polycomb group (PcG) proteins are chromatin modifiers that maintain transcriptional silencing, and loss of PcG genes causes widespread derepression of many developmentally important genes. However, because of their broad effects, the degree to which PcG proteins are used at specific fate choice points has not been tested. To understand how fate choices are maintained, we have been analyzing R7 photoreceptor neuron development in the fly eye. R1, R6, and R7 neurons are recruited from a pool of equivalent precursors. In order to adopt the R7 fate, these precursors make three binary choices. They: (1) adopt a neuronal fate, as a consequence of high receptor tyrosine kinase (RTK) activity (they would otherwise become non-neuronal support cells); (2) fail to express Seven-up (Svp), as a consequence of Notch (N) activation (they would otherwise express Svp and become R1/R6 neurons); and (3) fail to express Senseless (Sens), as a parallel consequence of N activation (they would otherwise express Sens and become R8 neurons in the absence of Svp). We were able to remove PcG genes specifically from post-mitotic R1/R6/R7 precursors, allowing us to probe these genes' roles in the three binary fate choices that R1/R6/R7 precursors face when differentiating as R7s. Here, we show that loss of the PcG genes Sce, Scm, or Pc specifically affects one of the three binary fate choices that R7 precursors must make: mutant R7s derepress Sens and adopt R8 fate characteristics. We find that this fate transformation occurs independently of the PcG genes' canonical role in repressing Hox genes. While N initially establishes Sens repression in R7s, we show that N is not required to keep Sens off, nor do these PcG genes act downstream of N. Instead, the PcG genes act independently of N to maintain Sens repression in R1/R6/R7 precursors that adopt the R7 fate. We conclude that cells can use PcG genes specifically to maintain a subset of their binary fate choices.